2022
DOI: 10.1200/op.21.00051
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Burnout Among Oncology Physician Assistants Between 2015 and 2019

Abstract: PURPOSE Burnout has significant implications for the individual provider, the oncology workforce, and the quality of care for patients with cancer. The primary aim of this study was to explore temporal changes in burnout among physician assistants (PAs) in oncology in 2019 compared with 2015. METHODS Oncology PAs were surveyed to assess for burnout using the Maslach Burnout Inventory according to the same cross-sectional design of the study performed in 2015. Comparison between oncology PAs in 2015 and 2019 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…22 Burnout was defined in this study as the presence of high score on the EE subscale (≥ 27) and/or a high score on the DP subscale (≥ 10). 15,20,21,23…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Burnout was defined in this study as the presence of high score on the EE subscale (≥ 27) and/or a high score on the DP subscale (≥ 10). 15,20,21,23…”
Section: Methodsmentioning
confidence: 99%
“…The MBI is considered the gold standard for assessment of burnout in health care providers and has been used extensively in studies exploring the well-being of various professions that make up the oncology team. [16][17][18][19][20][21] The MBI consists of 22 items and examines the key dimensions related to burnout with three subscales: emotional exhaustion (EE), depersonalization (DP), and sense of personal accomplishment. Using established cut-scores, scores were classified into high, moderate, or low levels for each subscale.…”
Section: Survey Dimensionsmentioning
confidence: 99%
“…This entire process can add significant additional time and logistic toxicity for patients and care partners, and also prescribers and pharmacists [ 2 , 6 , 8 , 11 ]. This is especially pertinent with record rates of clinician burnout [ 12 – 14 ], with a major contributor being administrative burdens of navigating supportive care medications [ 15 ]. Additional issues with using multiple pharmacies are decreased adherence [ 16 ], and safety concerns — prescription duplications and drug-drug interactions, especially if each individual pharmacy’s staff assumes that another pharmacy serves as the primary pharmacy for the patient, and is primarily responsible for checks.…”
Section: Discussionmentioning
confidence: 99%
“…Oncology PAs from the 2019 membership database of the Association of Physician Assistants in the Oncology were contacted to participate in a study on provider well-being and collaborative practice as previously reported. 13 Survey invitations were sent electronically using the research electronic data capture web-based survey platform. After providing electronic informed consent, all participants were invited to complete the full-length survey with three weekly reminder e-mails sent to potential participants who had not completed the full-length survey.…”
Section: Methodsmentioning
confidence: 99%